The role of non-coding RNAs in the regulation of stem cells and progenitors in the normal mammary gland and in breast tumors - Tordonato, Chiara; Di Fiore, Pier Paolo; Nicassio, Francesco (Frontiers in Genetics, 2015)
The outlook on stem cell biology is shifting from a rigid hierarchical to a more flexible model in which the identity and the behavior of adult stem cells (SCs), far from being a fixed feature, is determined by the dynamic integration of cell autonomous and non-autonomous mechanisms. Within this framework, the recent discovery of thousands of non-coding RNAs (ncRNAs) with regulatory function is redefining the landscape of transcriptome regulation, highlighting the interplay of epigenetic, transcriptional and post-transcriptional mechanisms in the specification of cell fate and in the regulation of developmental processes. Furthermore, the expression of ncRNAs is often tissue or even cell type-specific, emphasizing their function in defining space, time and developmental stages for gene regulation. Such a role has been investigated in embryonic and induced pluripotent stem cells and in numerous types of adult SCs and progenitors, including those of the breast, which will be the topic of this review. We will focus on ncRNAs with an important role in breast cancer, in particular in mammary cancer stem cells and progenitors, trying to highlight the ncRNA-based circuitries whose subversion alters a number of the epigenetic, transcriptional and post-transcriptional regulations responsible for the control of “stemness” in the physiological setting.